STRATEGI PEMASARAN DIGITAL DALAM PENERIMAAN SISWA - Ami Latifah; Yurna Dewi; Nasrudin Harahap; Nurul Hidayati Murtafiah (Journal of Islamic Education and Learning, 2022)
Along with the rapid development of technology and information, many schools have emerged by presenting new educational concepts. This makes schools in various places in Indonesia vying to make their schools so much in demand by students. This high level of competition makes school management need to formulate marketing strategies to increase interest in entering their educational institutions. In the era of the industrial revolution 4.0, the use of digital media as a means of communication is very relevant considering the target market, namely prospective students and parents of students, also uses the media a lot. Strategies that can be carried out by educational institutions in the context of marketing communication are: Publication (Publication and Publicity), Event (Programming events), News (Creating news), Community involvement (Caring for the community), Inform or image (Notifying or gaining an image) , Lobbying and Negotiation (Approach and Negotiation), Social Responsibility (social responsibility). Marketing optimization can be done by using digital media channels, including: utilizing school websites, school social media, online communities, email marketing and digital advertising.